Sex differences in the association of childhood socioeconomic position and later-life depressive symptoms in Europe: the mediating effect of education - Csajbók, Zsófia; Kagstrom, Anna; Kåreholt, Ingemar; Pawłowski, Bogusław; Marečková, Klára; Cermakova, Pavla (Social psychiatry and psychiatric epidemiology, 2021)
PURPOSE: We aimed to study sex differences in the association of childhood socioeconomic position (SEP) with later-life depressive symptoms, the mediating effect of education and explore regional differences across Europe. METHODS: The study included 58,851 participants (55% women, mean age 65 years) from the multicentre, population-based Survey on Health, Ageing and Retirement in Europe. Interviews were conducted in six waves and included measurements of childhood SEP (household characteristics at the age of 10) and depressive symptoms (EURO-D scale). Linear regression was used to study the association of childhood SEP with depressive symptoms, adjusting for covariates, and structural equation modelling assessed the mediating effect of education. RESULTS: In the fully adjusted model, higher childhood SEP was associated with lower depressive symptoms with a greater magnitude in women (B = - 0.07; 95% CI - 0.08, - 0.05) than in men (B = - 0.02; 95% CI - 0.03, - 0.00). Relative to men, childhood SEP had 3 times greater direct effect on depressive symptoms in women, and education had 3.7 times stronger mediating effect against childhood SEP. These associations and the sex differences were particularly pronounced in Southern, Central and Eastern Europe. CONCLUSION: Growing up in poor socioeconomic conditions is a stronger risk factor for the development of depressive symptoms for women than for men. Education may have a stronger preventive potential for women in reducing the adverse effects of childhood socioeconomic hardship. Central and Eastern European populations experience disproportionately higher risk of later-life depression due to lower SEP and greater sex differences.
Keywords: společenská třída; senioři; deprese; Europe; Mediation; Socioeconomic Factors; Social Class; Depression; Europe, Eastern; Evropa; mužské pohlaví; východní Evropa; socioekonomické faktory; Education; ženské pohlaví; Humans; Sex differences; Sex Characteristics; pohlavní dimorfismus; Aged; Female; Socioeconomic position; lidé; Male